A comparative analysis of East and West German labor markets before and after unification - Alan B. Krueger; Jörn-Steffen Pischke (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1992)
This paper uses micro data to analyze the wage structures in East Germany and West Germany before and after unification. In 1988, the wage distribution in East Germany was much more compressed than in West Germany or in the U.S. Since the collapse of Communism and unification with West Germany, however, the wage structure in eastern Germany has changed considerably. In particular, wage variation has increased, the payoff to education has decreased slightly, industry differentials have expanded, and the white collar premium has increased. Although average wage growth has been remarkably high in eastern Germany, individual variation in wage growth is similar to typical western levels. The wage structure of east Germans who work in west Germany resembles the wage structure of native west Germans in some respects, but the experience-earnings profile is flat.
Keywords: 330; Arbeitsmarkt; Deutschland; Neue Bundesländer